Architectural Storytelling and Disaster Awareness: Interpreting the Narrative of the Aceh Tsunami Museum Disaster Mitigation - Fitria Larasati; Cut Dewi; Elysa Wulandari; Mohd Sabrizaa Abd Rashid (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
This study explores how architectural narratives in the Aceh Tsunami Museum influence visitors’ understanding and awareness of disaster preparedness. Employing a descriptive qualitative method with museum narratology and Miles & Huberman’s interactive analysis, the research interprets how spatial design, symbolism, and sensory elements function as non-verbal educational media about the Tsunami disaster. Data were collected through participatory observation, in-depth interviews with curators, guides, and visitors, and analysis of curatorial documents. The findings reveal that the museum’s architecture constructs a sequential learning experience through three stages: affective (fear and empathy), reflective (prayer and contemplation), and cognitive (education and preparedness). Emotional engagement within dark and narrow spaces such as the tsunami corridor creates initial awareness of nature’s power, while reflective spaces like the Prayer Well foster empathy and moral reflection. Educational and simulation rooms integrate affective experiences with cognitive understanding, making disaster learning transformative rather than merely informative. The façade and Acehnese motifs further reinforce collective identity and cultural resilience, turning the museum into both a memorial and an educational laboratory. These results demonstrate that architectural narrative significantly enhances visitors’ comprehension and internalization of disaster awareness values. The study contributes to the development o architecture theory and disaster mitigation as wella s offers practical insights for designing museums and public spaces that integrate emotion, reflection, and cognition to strengthen disaster preparedness education.